Fabrication of aluminium internally cooled cutting tool by means of selective laser melting (SLM) - Mohd Hafizu, Zakaria; Saiful Anwar, Che Ghani; Wan Sharuzi, Wan Harun; Zuriadi, Zaulkafilai; Siti Rohaida, Mohamed (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2017)
A study of aluminium internally cooled cutting tool (ICCT) fabrication by means of selective laser melting is presented, including mechanical property's characterization and physical accuracy considerations. Mechanical performance is first performed on samples with simple geometry to determine density and mechanical strength using aluminium powders. SLM parameters such as laser scanning velocity, laser power and scanning strategy used are default from a machine manufacturer. Physical tests on the actual internal channel of an innovative internally cooled cutting tool such as a channel dimensional accuracy and surface roughness measurement are performed to define quality of the internal cooling channel affected by default process parameters with negligible microstructural defects. The internally cooled cutting tool is then tested in machining mild steel with recommended finishing cutting parameters to confirm its functional integrity and performance.